What is said is more important than who says it: an experimental study of content and prestige biases in social learning - Berl, Richard E. W., author; Samarasinghe, Alarna N., author; Roberts, Sean G., author; Gavin, Michael C., author; Jordan, Fiona M., author; Gray, Russell D., author (Colorado State University. Libraries, 2017)
Every human on our planet belongs to a culture, and we all begin to learn this information very early in life. But to accomplish this, we each have some very important decisions to make: What do we learn and who do we learn it from? And what do we do when these signals compete for our attention? To answer this, we used speakers of high and low prestige and two artificially constructed creation stories to test what information people use. Our findings may upturn our understanding of how humans learn and behave, and how our extraordinary capacity for culture evolved.
036 - Richard E Berl
Stories of prestige, creation, and the evolution of culture
Keywords: cultural evolution; social learning; content bias; prestige bias; creation stories; cultural transmission; experimental